Figures of speech in the language of Y. Yanovsky's novel "Horsemen" - Угненко, Ксенія Сергіївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2019)
The article deals with figures of speech as the exponents of the writer`s individual style. The expressive possibilities and structure of linguistic and stylistic constructions are analyzed. Found out the influence of the figures, inputting to the text on the change of modal, grammatical and expressive components of the whole phrase. Structural changes in the syntactic organization of literary expressions can be investigated through their interaction with other stylistic figures - asyndeton, palillogy. The article also focuses on the constructions which helped the author to implement the emotionally-expressive coloring to the work most accurately. The stylistic-syntactic emphasis is made on rhetorical questions and appeals in combination with other stylistic figures - so they give to the text bright neoromantic sounding, at the same time combining it both syntactically and semantically, providing artistic expressiveness and a significant aesthetic influence on the reader. Partly in the article the relationship between formal and semantic content of individual linguistic units of a work is investigated. A compulsory characteristic of rhetorical figures is the construction of such verbal rotations, which are conditionally dialogical in nature. Among such pieces of speech, scholars identify questions, questions, statements, objections, and excerpts. It is worth noting that rhetorical designs are not as simple and transparent as they seem at first glance. Introduction to the text of rhetorical figures - is an indispensable interaction of modal, intonational, grammatical and expressive components of the phrase. The main figures of the language can be grouped according to function, role in the language, as well as the nature of the syntactic organization.